Case Report: A Case of Late-Onset Combined Methylmalonic Acidemia and Hyperhomocysteinemia Induced by a Vegetarian Diet - Xu, Bei; Zhang, Lihong; Chen, Qiang; Wang, Yajuan; Peng, Yahong; Tang, Hui (Frontiers in Pediatrics, 2022)
Methylmalonic acidemia is a rare autosomal recessive metabolic disease. However, because of the atypical clinical symptoms, the type of late onset methylmalonic academia is often misdiagnosed. Especially when the blood vitamin B12 and folic acid levels are normal, it is not easy to think of this disease. Herein we report a 9-year-old girl who developed normally on a relatively balanced diet before 7 years of age. However, she presented with fatigue and attention deficit when she followed a vegetarian diet. Laboratory examination showed moderate macrocytic anemia, high levels of homocysteine, high level of propionylcarnitine/acetylcarnitine, urinary methylmalonic acid and methyl citrate. Gene mutation analysis showed c.609G > A and c.80A > G compound heterozygous mutations in the MMACHC gene, supported late-onset methylmalonic academia with homocysteinemia. Then treatment performed with add meat to the diet, vitamin B12, folic acid betaine and L-carnitine supplement. One week later, the child's clinical symptoms and the laboratory examinations were significantly improved.